BCL-2 Inhibitor Venetoclax Induces Autophagy-Associated Cell Death, Cell Cycle Arrest, and Apoptosis in Human Breast Cancer Cells - Ali Alhoshani (3720718) (2020)
Introduction Venetoclax (VCX) is a selective BCL-2 inhibitor approved for the treatment of leukemia and lymphoma. However, the mechanisms of anti-cancer effect of VCX either as a monotherapy or in combination with other chemotherapeutic agents against breast cancer need investigation. Methods Breast cancer cell lines with different molecular subtypes (MDA-MB-231, MCF7, and SKBR-3) were treated with different concentrations of VCX for indicated time points. The expression of cell proliferative, apoptotic, and autophagy genes was determined by qRTPCR and Western blot analyses. In addition, the percentage of MDA-MB-231 cells underwent apoptosis, expressed higher oxidative stress levels, and the changes in the cell cycle phases were determined by flow cytometry. Results Treatment of human breast cancer cells with increasing concentrations of VCX caused a significant decrease in cells growth and proliferation. This effect was associated with a significant increase in the percentage of apoptotic MDA-MB-231 cells and in the expression of the apoptotic genes, caspase 3, caspase 7, and BAX, with inhibition of antiapoptotic gene, BCL-2 levels. Induction of apoptosis by VCX treatment induced cell cycle arrest at G0/G1 phase with inhibition of cell proliferator genes, cyclin D1 and E2F1. Furthermore, VCX treatment increased the formation of reactive oxygen species and the expression level of autophagy markers, Beclin 1 and LC3-II. Importantly, these cellular changes by VCX increased the chemo-sensitivity of MDA-MB-231 cells to doxorubicin. Discussion The present study explores the molecular mechanisms of VCX-mediated inhibitory effects on the growth and proliferation of TNBC MDA-MB-231 cells through the induction of apoptosis, cell cycle arrest, and autophagy. The study also explores the role of BCL-2 as a novel targeted therapy for breast cancer. Other Information Published in: OncoTargets and Therapy License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.2147/ott.s281519